2019
DOI: 10.1016/j.onehlt.2019.100103
|View full text |Cite
|
Sign up to set email alerts
|

Impact of One-Health framework on vaccination cost-effectiveness: A case study of rabies in Ethiopia

Abstract: Livestock losses due to rabies and health and the corresponding benefits of controlling the disease are not often considered when the cost-effectiveness of rabies control is evaluated. In this research, assessed the benefits of applying a One Health perspective that includes these losses to the case of canine rabies vaccination in Ethiopia. We constructed a dynamic epidemiological model of rabies transmission. The model was fit to district-specific data on human rabies exposures and canine demography for two d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 40 publications
0
15
0
Order By: Relevance
“…In recent years, researchers have been trying to identify external factors impacting the spatial dynamics of RABV spread ( n = 5) [ 63 , 64 , 68 , 69 , 71 ] ( Fig 2D and S1 Table ). Contrary to phylodynamic studies, the modelling category gathers a diverse panel of models with aims that cover the implementation of new mathematical methodologies ( n = 2) [ 42 , 46 ], the characterization of rabies dynamics ( n = 11) [ 26 , 27 , 31 , 32 , 40 , 41 , 44 , 47 49 , 51 ], the identification of factors driving the resurgence or maintenance of rabies ( n = 9) [ 16 , 23 , 25 , 33 35 , 37 , 38 , 43 ], the assessment of control strategies efficacy ( n = 18) [ 16 , 23 , 24 , 27 29 , 31 , 33 36 , 42 45 , 49 51 ], the risk assessment of rabies introduction and the evaluation of outbreak preparedness in rabies-free areas ( n = 3) [ 30 , 36 , 42 ], and cost-effectiveness studies ( n = 2) [ 39 , 48 ] ( Fig 2D and…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, researchers have been trying to identify external factors impacting the spatial dynamics of RABV spread ( n = 5) [ 63 , 64 , 68 , 69 , 71 ] ( Fig 2D and S1 Table ). Contrary to phylodynamic studies, the modelling category gathers a diverse panel of models with aims that cover the implementation of new mathematical methodologies ( n = 2) [ 42 , 46 ], the characterization of rabies dynamics ( n = 11) [ 26 , 27 , 31 , 32 , 40 , 41 , 44 , 47 49 , 51 ], the identification of factors driving the resurgence or maintenance of rabies ( n = 9) [ 16 , 23 , 25 , 33 35 , 37 , 38 , 43 ], the assessment of control strategies efficacy ( n = 18) [ 16 , 23 , 24 , 27 29 , 31 , 33 36 , 42 45 , 49 51 ], the risk assessment of rabies introduction and the evaluation of outbreak preparedness in rabies-free areas ( n = 3) [ 30 , 36 , 42 ], and cost-effectiveness studies ( n = 2) [ 39 , 48 ] ( Fig 2D and…”
Section: Resultsmentioning
confidence: 99%
“…In Ethiopia, Beyene et al ( 8 ) estimated the cost-effectiveness of mass vaccination in representative urban and rural districts while accounting for human health impacts as well as livestock impacts. This particular study simulated over the period of 5 years identified vaccination coverages of 70 and 80% to be the most likely to provide the greatest net health benefits in urban and rural districts, respectively.…”
Section: Implications On the Economics Of Controlmentioning
confidence: 99%
“…In other words, the cost of the mass vaccination campaign is less than the total financial loss associated with rabies, which includes cattle-related rabies. On the other hand, the active investigation to identify other bite victims also comes at an reasonable additional cost to the program, which was not included in the cost accounting of the study ( 8 ). Similar studies need to consider at least costs of risk-based investigation, although implementation has been difficult for many countries including Ethiopia where funding for dog vaccination is limited.…”
Section: Implications On the Economics Of Controlmentioning
confidence: 99%
See 2 more Smart Citations